Edukasi kesehatan tentang alat kontrasepsi dalam rahim (KB AKDR) pada wanita usia subur - Wedharing Sekar Asmarani; Gunarmi Gunarmi; Zesika Intan Navelia (JOURNAL of Public Health Concerns, 2026)
Background: The Intrauterine Device (IUD) is the most effective long-acting reversible contraceptive (LARC) method; however, its uptake remains low—including within the service area of ​​the Cisoka Community Health Center due to a lack of knowledge among women of reproductive age. Proper understanding is essential for these women to select and decide on the appropriate contraceptive method. A solid understanding helps increase knowledge, foster positive attitudes, and correct misconceptions regarding family planning methods. Purpose: To increase knowledge about IUD contraception among women of reproductive age as an effort to boost the number of family planning acceptors. Method: The activity was conducted on April 28, 2026, in the service area of ​​the Cisoka Community Health Center, Tangerang Regency, involving 30 respondents (women of reproductive age). A direct, participatory educational approach was employed, utilizing lectures supported by leaflets. Levels of knowledge and understanding were assessed using a one-group pretest-posttest design, with questionnaires administered before (pretest) and after (posttest) the educational session. Evaluation involved analyzing the aggregated questionnaire data and descriptively reporting the respondents' level of understanding regarding IUD contraception. Results: The results showed that the respondents' mean age was 34.03 years, with the majority (73.3%) falling within the 30–39 age range. Most respondents (63.3%) had a high school education, and the majority (73.3%) were housewives. Questionnaire analysis revealed an improvement in respondents' knowledge regarding IUD contraception: the proportion of respondents in the "sufficient" knowledge category shifted from 70.0% before the educational activity to 80.0% in the "good" category after the activity. Conclusion: Educational activities utilizing a participatory approach and leaflets were highly effective in increasing the knowledge of women of reproductive age regarding the benefits of IUD contraception. Enhanced understanding of health aspects associated with IUD use motivated these women and encouraged community uptake of the method; this benefits family health by effectively preventing long-term pregnancy, reducing maternal mortality rates, and averting future health complications for the family. Suggestion: Health facilities are encouraged to collaborate with community health volunteers to provide periodic, sustained education that reaches a wider audience, thereby boosting the number of IUD users. Additionally, Community Health Centers should provide consultation services regarding contraceptive use and address misconceptions prevalent in the community. Keywords: Contraceptive acceptors; IUD contraception; Leaflets; Women of reproductive age Pendahuluan: Alat kontrasepsi dalam rahim (AKDR) merupakan metode kontrasepsi jangka panjang (MKJP) yang paling efektif, namun cakupan penggunanya masih rendah, termasuk di wilayah kerja Puskesmas Cisoka, akibat kurangnya pengetahuan wanita usia subur (WUS). Pemahaman bagi wanita usia subur (WUS) sangat diperlukan dalam pemilihan dan menentukan alat kontrasepsi yang tepat. Pemahaman yang baik membantu meningkatkan pengetahuan, mengubah sikap positif, dan meluruskan persepsi keliru tentang metode KB. Tujuan: Untuk meningkatkan pengetahuan tentang KB AKDR kepada wanita usia subur (WUS) sebagai upaya peningkatan akseptor KB. Metode: Kegiatan dilaksanakan pada 28 April 2026 di wilayah kerja Puskesmas Cisoka Kabupaten Tangerang. Melibatkan 30 responden yang merupakan wanita usia subur. Kegiatan menggunakan pendekatan edukatif partisipatif langsung yang disampaikan melalui ceramah dan dibantu media leaflet. Pengukuran tingkat pengetahuan dan pemahaman responden dilakukan dengan pendekatan one group pretest and posttest design menggunakan kuesioner yang diberikan sebelum (pretest) dan sesudah kegiatan edukasi (posttest). Evaluasi kegiatan dilakukan dengan menganalisa hasil akumulasi kuesioner dan disampaikan secara deskriptif terkait tingkat pemahaman responden tentang KB AKDR. Hasil: Menunjukkan bahwa usia rata-rata responden adalah 34.03 tahun dan mayoritas berada direntang usia 30-39 tahun sebesar 73.3%. Sebagian besar tingkat pendidikan responden adalah Sekolah Menengah Atas yaitu sebesar 63.3% dan mayoritas status pekerjaan responden adalah ibu rumah tangga yaitu sebesar 73.3%. Sedangkan analisa kuesioner menunjukkan terdapat peningkatan pengetahuan responden tentang KB AKDR dari sebelum kegiatan edukasi adalah sebesar 70.0% kategori cukup menjadi sebesar 80.0% kategori baik setelah kegiatan edukasi. Simpulan: Kegiatan penyuluhan melalui pendekatan partisipatif dengan berbasis leaflet sangat efektif meningkatkan pengetahuan WUS tentang manfaat KB AKDR. Peningkatan pemahaman tentang kesehatan melalui penggunaan AKDR juga memberikan motivasi WUS dan mendorong masyarakat sebagai akseptor AKDR yang bermanfaat bagi kesehatan keluarga karena efektif mencegah kehamilan jangka panjang, menekan angka kematian ibu, dan mencegah komplikasi masalah kesehatan keluarga di masa datang. Saran: Diharapkan kepada fasilitas kesehatan dengan melibatkan kader untuk memberikan edukasi secara berkala dan berkelanjutan dengan jangkauan masyarakat yang lebih luas sehingga dapat mendorong peningkatan jumlah akseptor AKDR. Diharapkan juga pada Puskesmas untuk menyediakan tempat konsultasi kepada masyarakat terkait penggunaan alat kontrasepsi dan memberikan solusi dari permasalahan miskonsepsi yang terjadi di masyarakat.